Reduced Na(+) Affinity Increases Turnover of Salmonella enterica Serovar Typhimurium MelB - Jakkula, S. Vivek (American Society for Microbiology, 2012)
The melibiose permease of Salmonella enterica serovar Typhimurium (MelB(St)) catalyzes symport of melibiose with Na(+), Li(+), or H(+). Bioinformatics and mutational analyses indicate that a conserved Gly117 (helix IV) is a component of the Na(+)-binding site. In this study, Gly117 was mutated to Ser, Asn, or Cys. All three mutations increase the maximum rate (V(max)) for melibiose transport in Escherichia coli DW2 and greatly decrease Na(+) affinity, indicating that intracellular release of Na(+) is facilitated. Rapid melibiose transport, particularly by the G117N mutant, triggers osmotic lysis in the lag phase of growth. The findings support the previous conclusion that Gly117 plays an important role in cation binding and translocation. Furthermore, a spontaneous second-site mutation (P148L between loop(4-5) and helix V) in the G117C mutant prevents cell lysis. This mutation significantly decreases V(max) with little effect on cosubstrate binding in G117C, G117S, and G117N mutants. Thus, the P148L mutation specifically inhibits transport velocity and thereby blocks the lethal effect of elevated melibiose transport in the Gly117 mutants.